Aquagenic Wrinkling of the Palms and Mutations in the Cystic Fibrosis Gene: A Diagnostic Clue - Ferreira,Marli (2021)
Abstract Described for the first time in 1974, aquagenic wrinkling of the palms (AWP) is an entity characterized by pruritic wrinkling of the palms with associated oedema after brief contact with water. It was first noticed in children diagnosed with cystic fibrosis and in the last years the association between these conditions has been established. We report a case of a 21-year-old Caucasian woman with history of chronic rhinosinusitis and with a clinical diagnosis of AWP. The conducted study revealed a heterozygous mutation for p.Phe508del in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. AWP might represent a feature of CFTR mutation and its identifica-tion should lead to a full genetic test counselling.